2022
DOI: 10.1093/cdn/nzac051.044
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Common in the Orthopedic Trauma Population: A Multicenter Cross-Sectional Study

Abstract: Objectives Malnutrition increases the risk for adverse outcomes after musculoskeletal trauma. Food insecurity is an increasingly recognized risk factor for malnutrition. The purpose of this investigation is to evaluate the prevalence and risk factors for food insecurity in a diverse population treated for operative fracture fixation. Methods A two-center study (Midwest and Pacific Northwest) enrolled participants of any age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Other recent studies investigating food insecurity in the orthopaedic population have estimated proportions between approximately 13% and 25% [1, 8]. The recorded proportion in these patients was much higher, at 37%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other recent studies investigating food insecurity in the orthopaedic population have estimated proportions between approximately 13% and 25% [1, 8]. The recorded proportion in these patients was much higher, at 37%.…”
Section: Discussionmentioning
confidence: 98%
“…Food insecurity is associated with malnutrition in older patients [16], which has important implications, because malnutrition has been linked to a higher risk of complications in patients with musculoskeletal conditions [14]. Recent reports have suggested that patients who have experienced orthopaedic trauma may be at increased risk of food insecurity compared with the national mean [7,8,18]. This may be in part because of the socioeconomic implications that sustaining a traumatic orthopaedic injury has on a patient, including temporary or permanent loss of employment and wages and decreased mobility.…”
Section: Introductionmentioning
confidence: 99%